Effectiveness of celebrity endorsement in India - Kaur, Rajbir (2014)
In today’s world, where advertising plays an inevitable role in influencing consumer purchase decisions, it becomes imperative for companies to create such advertising campaigns that motivate consumers to buy their products. Celebrity Endorsement is a technique extensively used by companies today, to promote their brand and products, which help in generating publicity for their brands. These ‘celebrities’ are typically the famous and successful actors or sportspeople who are looked up to by the common people.